The bristle pattern development in Drosophila melanogaster: the prepattern and achaete-scute genes - D. P. Furman; T. V. Bukharina (Вавиловский журнал генетики и селекции)
The external drosophila mechanoreceptors, residing on the head and body of imago, are represented by bristles of diﬀerent sizes (macrochaetes and microchaetes). Macrochaetes are arranged in the species-specifc bristle pattern, where each of them is strictly positioned. The bristle pattern is formed starting from its prototype (prepattern) in the imaginal disc. The position specifcity of future mechanoreceptors is determined by local expression of two proneural genes, achaete (ac) and scute (sc) belonging to the AS-C complex, in response to the action of certain factors, referred to as prepattern factors, nonuniformly distributed in the ectoderm of imaginal discs. The topography of their total distribution defnes the bristle prepattern. Thus, the full-ﬂedged adult bristle pattern is the result of interaction of two systems – the prepattern and the system responding to prepattern, i. e., the achaete and scute genes. A considerable volume of miscellaneous experimental data related to various aspects in development of the bristle pattern has been so far accumulated; however, any formalized and detailed representation of the molecular genetic interaction of the prepattern factors with both each other and the achaete-scute genes is yet absent. This review systematizes the available data on the regular patterns of this interaction and shows that local expression of these genes is determined by hierarchical two-level control system comprising both direct and indirect regulators of their activities. A generalized scheme of the system containing the functional interactions of its components is proposed. The structural organization and principles of operation of the hierarchical molecular genetic system enabling the local expression of ASC genes and the resulting formation of ordered bristle pattern are described.